2012
DOI: 10.1186/1471-2350-13-39
|View full text |Cite
|
Sign up to set email alerts
|

TGFB1 genetic polymorphisms and coronary heart disease risk: a meta-analysis

Abstract: BackgroundGenetic variations in TGFB1 gene have been studied in relation to coronary heart disease (CHD) risk, but the results were inconsistent.MethodsWe performed a systematic review of published studies on the potential role of TGFB1 genetic variation in CHD risk. Articles that reported the association of TGFB1 genetic variants with CHD as primary outcome were searched via Medline and HuGE Navigator through July 2011. The reference lists from included articles were also reviewed.ResultsData were available f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 64 publications
0
19
0
6
Order By: Relevance
“…Several genome-wide association studies (GWAS) have identified an association between CAD and single nucleotide polymorphisms (SNPs) in genes encoding TGFβ signalling pathway components. For example, functional polymorphisms in the promoter, signal peptide sequence and coding sequence of the TGFβ1 gene are associated with increased risk of myocardial infarction [ 64 , 65 ]) and stroke [ 66 ]; meta-analyses have also shown an association between these polymorphisms and CAD [ [67] , [68] , [69] , [70] ]. In addition, a joint analysis of two GWAS on CAD patients identified an association with an intronic SNP in the SMAD3 gene [ 71 ] which was later shown to reduce enhancer activity and attenuate Smad3 expression [ 72 , 73 ].…”
Section: Tgfβ In Coronary Artery Diseasementioning
confidence: 99%
“…Several genome-wide association studies (GWAS) have identified an association between CAD and single nucleotide polymorphisms (SNPs) in genes encoding TGFβ signalling pathway components. For example, functional polymorphisms in the promoter, signal peptide sequence and coding sequence of the TGFβ1 gene are associated with increased risk of myocardial infarction [ 64 , 65 ]) and stroke [ 66 ]; meta-analyses have also shown an association between these polymorphisms and CAD [ [67] , [68] , [69] , [70] ]. In addition, a joint analysis of two GWAS on CAD patients identified an association with an intronic SNP in the SMAD3 gene [ 71 ] which was later shown to reduce enhancer activity and attenuate Smad3 expression [ 72 , 73 ].…”
Section: Tgfβ In Coronary Artery Diseasementioning
confidence: 99%
“…In their meta-analysis, only seven individual studies were included. Among these included individual studies, one study by Sie deviating from the HWE was not excluded (Lu et al, 2012 ). Hence, the results from the two above meta-analysises published before were not as accurate as that deduced from the current meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Many other environmental factors as age, smoke, gender, obesity, dyslipidemia, diabetes mellitus, and hypertension might affect the CAD development. Since these factors were not matched in most of individual studies, it was difficult to analyze their effect on the CAD progress (Lu et al, 2012 ). Additionally, according to our knowledge it is >1000-fold confirmed association between given polymorphism and the risk of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TGF-β1 has been implicated in the pathogenesis of autoimmune disease, carcinogenesis, and cardiovascular disease 24 . Evidence indicates that TGF-β is implicated in cardiovascular disease with significantly higher plasma levels of activated TGF-β in patients with coronary heart disease 25 . We hypothesize that memantine increased the activation of the immune response to heroin and methadone use by maintaining the plasma TGF-β1 levels.…”
Section: Discussionmentioning
confidence: 99%